Okay, so first we distribute 6 to (5a+4)
Therefore it's 5a(6) + 4(6)
which is equal to: 30a+24
the equation is now -11-5a = 30a+24
To get a, we transpose -11 to the right side, and remember the rule that when you transpose, you have to change the sign therfore it becomes +11 and it now looks like this:
-5a = 30a+24+11
then next, we transpose 30a to the left side and it becomes -30a
then it looks like this
-5a-30a = 24+11
we solve this and we get
-35a = 35
we divide both sides by -35 to get "a"
-35a/-35 = 35/-35
compute that and we get
a = -1
which is the final answer.
Hope I helped :D
Content will be erased after question is completed.
Enter the email address associated with your account, and we will email you a link to reset your password.
Forgot your password?